Analysis of Differentiation, Quality and Price Strategies on Competitive Advantages and Their Effect on Customer Satisfaction of Noodle Products PT Sukabumi Alam Mandiri - Tony Justinus Hoetama; Damelina Basauli Tambunan (Journal Research of Social Science, Economics, and Management, 2025)
This research aims to analyze the effect of differentiation strategy, product quality, and price on competitive advantage, and its impact on marketing performance of PT Wings Group's instant noodle products. In the Fast Moving Consumer Goods (FMCG) industry, intense competition forces companies to continuously innovate and offer added value to consumers. Competitive advantage becomes a key factor in maintaining market share and enhancing marketing performance, especially in the highly competitive instant noodle product category. This research uses a quantitative approach with data collected through surveys from consumers of PT Wings instant noodle products. The analysis was conducted using a multiple regression analysis model to examine the influence of differentiation strategy, product quality, and price on competitive advantage, as well as the relationship between competitive advantage and marketing performance. This study is expected to provide insights into how elements of differentiation strategy, product quality, and price can create a significant competitive advantage and positively impact marketing performance. The findings are expected to serve as a guide for the company to develop more effective strategies in facing competition in the FMCG market.